Virtual discovery of melatonin receptor ligands to modulate circadian rhythms - Stein, Reed M.; Kang, Hye Jin; McCorvy, John D.; Glatfelter, Grant C.; Jones, Anthony J.; Che, Tao; Slocum, Samuel; Huang, Xi-Ping; Savych, Olena; Moroz, Yurii S.; Stauch, Benjamin; Johansson, Linda C.; et al. (Nature (London), 2020)
The neuromodulator melatonin synchronizes circadian rhythms and related physiological functions through the actions of two G-protein-coupled receptors: MT 1 and MT 2 . Circadian release of melatonin at night from the pineal gland activates melatonin receptors in the suprachiasmatic nucleus of the hypothalamus, synchronizing the physiology and behaviour of animals to the light–dark cycle 1 – 4 . The two receptors are established drug targets for aligning circadian phase to this cycle in disorders of sleep 5 , 6 and depression 1 – 4 , 7 – 9 . Despite their importance, few in vivo active MT 1 -selective ligands have been reported 2 , 8 , 10 – 12 , hampering both the understanding of circadian biology and the development of targeted therapeutics. Here we docked more than 150 million virtual molecules to an MT 1 crystal structure, prioritizing structural fit and chemical novelty. Of these compounds, 38 high-ranking molecules were synthesized and tested, revealing ligands with potencies ranging from 470 picomolar to 6 micromolar. Structure-based optimization led to two selective MT 1 inverse agonists—which were topologically unrelated to previously explored chemotypes—that acted as inverse agonists in a mouse model of circadian re-entrainment. Notably, we found that these MT 1 -selective inverse agonists advanced the phase of the mouse circadian clock by 1.3–1.5 h when given at subjective dusk, an agonist-like effect that was eliminated in MT 1 - but not in MT 2 -knockout mice. This study illustrates the opportunities for modulating melatonin receptor biology through MT 1 -selective ligands and for the discovery of previously undescribed, in vivo active chemotypes from structure-based screens of diverse, ultralarge libraries. A computational screen of an ultra-large virtual library against the structure of the melatonin receptor found nanomolar ligands, and ultimately two selective MT 1 inverse agonists that induced phase advancement of the mouse circadian clock when given at subjective dusk.